ANALISIS LAPORAN ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PADA PT ASHAHIMAS FLAT GLASS TBK SIDOARJO - Muhammad Riduwan (Gapenas Publisher, 2022)
Cash is a company asset that plays an important role in financing the company's operational activities. The cash flow statement contains information about the actual cash position in operating business activities. with the cash flow ratio we can analyze how the evolution of the company's financial performance from year to year. The purpose of this study was to determine the use of cash flow statements to assess the financial performance of PT. Ashhimas Flat Glass Tbk Sidoarjo, using a qualitative descriptive method. The results showed that the cash flow ratio showed a low number, meaning that the financial performance of PT. Ashhimas Flat Glass Tbk Sidoarjo is in bad condition. increasing the company's liquidity is important for PT. Ashhimas Flat Glass, Tbk Sidoarjo especially in operational activities which are the company's main activities so that in the future the company's financial performance will increase